2017
DOI: 10.1016/j.jhydrol.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven variability in the occurrence of major floods across North America and Europe

Abstract: Concern over the potential impact of anthropogenic climate change on flooding has led to a proliferation of studies examining past flood trends. Many studies have analysed annual-maximum flow trends but few have quantified changes in major (25-100 year return period) floods, i.e. those that have the greatest societal impacts. Existing major-flood studies used a limited number of very large catchments affected to varying degrees by alterations such as reservoirs and urbanisation. In the current study, trends in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 70 publications
(70 reference statements)
4
126
0
3
Order By: Relevance
“…Peaks for the American River time series are apparent at 2.3 and 15 years and in the LBDA time series at approximately 8, 20, and 64 years. A detailed analysis of these time series is beyond the scope of this paper, but we note that the high amplitude and long time periods of the quasiperiodic oscillations they exhibit are consistent with analyses of LFV in other hydroclimate systems (Hodgkins et al, 2017;Kiem et al, 2002;Swierczynski et al, 2012;Woollings et al, 2014). A detailed analysis of these time series is beyond the scope of this paper, but we note that the high amplitude and long time periods of the quasiperiodic oscillations they exhibit are consistent with analyses of LFV in other hydroclimate systems (Hodgkins et al, 2017;Kiem et al, 2002;Swierczynski et al, 2012;Woollings et al, 2014).…”
Section: Planning Decisions Are Made With Finite Horizonssupporting
confidence: 73%
“…Peaks for the American River time series are apparent at 2.3 and 15 years and in the LBDA time series at approximately 8, 20, and 64 years. A detailed analysis of these time series is beyond the scope of this paper, but we note that the high amplitude and long time periods of the quasiperiodic oscillations they exhibit are consistent with analyses of LFV in other hydroclimate systems (Hodgkins et al, 2017;Kiem et al, 2002;Swierczynski et al, 2012;Woollings et al, 2014). A detailed analysis of these time series is beyond the scope of this paper, but we note that the high amplitude and long time periods of the quasiperiodic oscillations they exhibit are consistent with analyses of LFV in other hydroclimate systems (Hodgkins et al, 2017;Kiem et al, 2002;Swierczynski et al, 2012;Woollings et al, 2014).…”
Section: Planning Decisions Are Made With Finite Horizonssupporting
confidence: 73%
“…Ward et al (2016) and Emerton et al (2017) have previously demonstrated the role of ENSO in modulating global floods. In addition, Hodgkins et al (2017) demonstrated recently that AMO has a significant negative (positive) relationship with 25-and 50-year flood occurrence for large (medium) catchments in North America (Europe).…”
Section: Millionsmentioning
confidence: 96%
“…Banasik et al 2013;Ilnicki et al 2014;Kędra 2017;Miler 2015;Somorowska 2017) or small regions (NiedĹşwiedĹş et al 2015;Ruiz-Villanueva et al 2016;Sen and Niedzielski 2010), with one notable exception of Wrzesiński and Sobkowiak (2018) who analysed long-term changes (but not trends) in flow regime of 159 flow gauges with a good geographical coverage in Poland. Polish rivers were not included in several pan-European (Hannaford et al 2013;Stahl et al 2010) or global (Hodgkins et al 2017) studies on trend detection, perhaps due to restrictive data sharing policy . In summary, a need for a comprehensive trend detection study for Polish river flows is well motivated.…”
Section: Introductionmentioning
confidence: 99%